Cultivating a just habitus through intercultural wisdom of women - Choi, Heejin (British Journal of religious education, 2025)
This article explores the possibility of cultivating a just habitus through intercultural wisdom of women in religious education. Drawing insights from different cultural and feminist perspectives, it highlights the transformative power of the intercultural wisdom of women. Black womanist voices emphasise creating safe spaces for communal lamentation and mutual support. White feminist perspectives stress the importance of confronting privilege and actively engaging in solidarity with women of colour. Asian feminist viewpoints underscore the interconnectedness and interdependence among culturally different people. These perspectives intersect to form a vibrant tapestry of intercultural wisdom of women, offering valuable lessons for religious education. The intercultural wisdom of women can help religious education become a transformative space for people to cultivate a just habitus.